(untitled) (Research Nepal Journal of Development Studies, 2018)
People’s livelihood in the villages of the middle hill of Nepal are based on farming system. The relationship between climate change and seasonal labor migration in the middle hill areas is a relatively understudied research topic, particularly from an empirical point of view. This article aims at contributing to the literature by analyzing the relationship between livelihoods and human mobility in two rural communities located in the Province 5, Arghakhanchi district, Nepal. Traditional rain-fed agriculture is the most important economic activity in the area. This article highlights differences in livelihood and human mobility patterns between households. The economy of the middle hill is primarily agrarian. Over 80% of the population of the middle hill districts still lives in rural areas/settings, where levels of poverty are higher than in the neighbouring countries. They depend on farming and collecting forest products for their livelihoods. In Arghakhanchi district, during the dry season, many migrate in search of temporary work as labourers particularly in Indian states. Arghakhanchi is the district where the proportion of inhabitants from low income is relatively higher than the other surrounding districts of Province 5. These people are marginalized and experience high rates of poverty, low levels of education and poor health. They are highly vulnerable to climate change, due to poverty and dependence on climate-sensitive livelihoods in a vulnerable region. Consequently, more households are likely to participate in seasonal migration and those already migrating are credible to do so for longer times. Currently, such migrants take up low-paying unskilled works, mainly in urban areas in Uttarakhand, Panjab and Bhopal of India, which enables them to make meager savings, hardly enough to repay the debt of their family has incurred during food shortages. In the study area, the non-agricultural diversification is widespread and income from non-agricultural activities exceeds agricultural income. However, though mobility patterns in the area are determined primarily by broader economic considerations. Research Nepal Journal of Development Studies Vol.1(1) 2018 42-57